2017
DOI: 10.1016/j.lfs.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of a recombinant humanized anti-cocaine monoclonal antibody's effects on cocaine pharmacokinetics in mice

Abstract: Aims A recombinant humanized anti-cocaine monoclonal antibody (mAb), h2E2, is at an advanced stage of pre-clinical development as an immunotherapy for cocaine abuse. It is hypothesized that h2E2 binds to and sequesters cocaine in the blood. Main Methods A three-compartment model of the effects of h2E2 on cocaine's distribution was constructed. The model assumes that h2E2 binds to cocaine and that the h2E2-cocaine complex does not enter the brain but distributes between the central and peripheral compartments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…The drastic inhibition of carboxylesterase-mediated metabolism of cocaine in the presence of the antibody is consistent with h2E2 acting as a chemical antagonist of cocaine. The seemingly paradoxical elimination of cocaine from the plasma in the presence of h2E2 in vivo may be resolved by investigating whether the observed decline in plasma concentration actually represents a slowed distribution phase (Wetzel et al, 2017 Formulation 2 while the same results against fungus, that is, Formulation 1 (4.5-cm ZI against rust while 5.0-cm against smut) was more effective than Formulation 2 (3.00-cm ZI against rust and 3.5-cm ZI against smut). Phytochemical analysis showed that garlic has organosulfur compounds (11-35 mgÁg −1 of fresh garlic), arginine, oligosaccharides, flavonoids, and selenium.…”
Section: Key Resultsmentioning
confidence: 99%
“…The drastic inhibition of carboxylesterase-mediated metabolism of cocaine in the presence of the antibody is consistent with h2E2 acting as a chemical antagonist of cocaine. The seemingly paradoxical elimination of cocaine from the plasma in the presence of h2E2 in vivo may be resolved by investigating whether the observed decline in plasma concentration actually represents a slowed distribution phase (Wetzel et al, 2017 Formulation 2 while the same results against fungus, that is, Formulation 1 (4.5-cm ZI against rust while 5.0-cm against smut) was more effective than Formulation 2 (3.00-cm ZI against rust and 3.5-cm ZI against smut). Phytochemical analysis showed that garlic has organosulfur compounds (11-35 mgÁg −1 of fresh garlic), arginine, oligosaccharides, flavonoids, and selenium.…”
Section: Key Resultsmentioning
confidence: 99%
“…Shoptaw et al [7] note the development of a recombinant humanized anti-cocaine monoclonal antibody [8] as a promising way forward. Particularly long-acting agents may offer a more sustainable model of care.…”
Section: How Can We Optimally Channel Therapeutic Optimism To Advancementioning
confidence: 99%
“…Nascent efforts in the field carry potential for success. One notable example involves medication development for cocaine overdose, a monoclonal antibody that sequesters cocaine in circulating blood [8]. An effective overdose medication would have significant health impact, an effect that perhaps could be boosted when co‐administered with an opioid reversal agent in emergency settings and with an overdose of opioids and/or cocaine.…”
mentioning
confidence: 99%
“…In addition to functional studies in rats and mice [ [2] , [3] , [4] , [5] ], our laboratory has also performed many structural and binding studies, using a variety of techniques [ 6 , 7 ]. We developed a method for measuring ligand binding by intrinsic mAb fluorescence quenching [ 8 ], as well as by ligand stabilization against thermal denaturation, using extrinsic fluorescent dyes and the differential scanning fluorimetry (DSF) method [ 9 ].…”
Section: Introductionmentioning
confidence: 99%